2018
DOI: 10.1097/mbc.0000000000000680
|View full text |Cite
|
Sign up to set email alerts
|

Effects of malignancy on blood coagulation in septic intensive care patients

Abstract: : The objectives of the study are to examine the effect of sepsis on the coagulation profile of patients having solid cancer and to test the hypothesis that septic patients with cancer have normal or increased hemostatic capacity despite prolonged standard coagulation tests (SCTs) compared with noninfected cancer patients. Patients with solid cancer were included in the study forming two groups: study group included patients with sepsis with minimum two organ dysfunctions and control group formed by noninfecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Hypercoagulability is common in patients with malignant tumor [6]. Tumor cells can damage the vascular endothelium, strengthen the adhesion, aggregation and activation of platelets, secrete procoagulant substances, reduce anticoagulant activity, inhibit the activation of fibrinolytic system, and cause hypercoagulable state [7].…”
Section: Discussionmentioning
confidence: 99%
“…Hypercoagulability is common in patients with malignant tumor [6]. Tumor cells can damage the vascular endothelium, strengthen the adhesion, aggregation and activation of platelets, secrete procoagulant substances, reduce anticoagulant activity, inhibit the activation of fibrinolytic system, and cause hypercoagulable state [7].…”
Section: Discussionmentioning
confidence: 99%
“…Massion et al proposed that the increased fibrinogen concentration in septic patients may explain the discrepancy between low platelet levels and normal maximum clot firmness in thromboelastometry by compensating for thrombocytopenia or for decreased coagulation factor activity. ( 13 , 14 )…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, few studies have shown the utility of derived ROTEM parameters in assessing coagulation kinetics. These parameters are beginning to be used in septic patients with multiple system organ failure with promising results [13]. Solomon et al [14] demonstrated that clot elasticity and clot firmness did not follow a linear correlation and that the use of clot elasticity could prove to offer a more significant insight into clot strength.…”
Section: Discussionmentioning
confidence: 99%